The role of intuition in ethical reflection: exploratory research into ethics reflection groups. Issue 1 (2nd January 2020) - Van Seggelen – Damen, Inge; Westerveld, Judy
ABSTRACT: In an interview study with ambulance nurses who participated in Ethics Reflection Groups (ERGs), we explored what role intuition plays in ethical reflection and we examined whether intuition and reflection can be separated both conceptually and empirically. Based on the literature it can be argued that in certain situations, rational thinking gives better results, whereas intuition excels in other situations. Our study demonstrates, however, that an unambiguous and complete explanation for the conceptual differences and outcomes is lacking. The literature hardly discusses intuition, nor its relationship to ethical reflection. Nevertheless, interviewed ambulance nurses do recognize the use of both reflection and intuition in ethical reflection. They talk regularly with colleagues about practical cases and explicate that they combine intuition with reflection induced by professional protocols. Intuition appears to be a form of reflection-in-action dictated by timing or time available, whereas reflection involves reflection-on-action. During ethical reflection in ERGs, previous use of intuition is tested afterwards on the basis of rational arguments. As such, reflection-on-action provides the opportunity to learn from experiences and to gain insight into one's own actions and, thus, to facilitate sensemaking and reflection-in-action in future situations.